Localized populations of CD8 MHC class I tetramer SIV-specific T cells in lymphoid follicles and genital epithelium. - Jung Joo Hong; Matthew R Reynolds; Teresa L Mattila; Aaron Hage; David I Watkins; Christopher J Miller; Pamela J Skinner (PLoS ONE, 2009)
CD8 T cells play an important role in controlling viral infections. We investigated the in situ localization of simian immunodeficiency virus (SIV)-specific T cells in lymph and genital tissues from SIV-infected macaques using MHC-class I tetramers. The majority of tetramer-binding cells localized in T cell zones and were CD8(+). Curiously, small subpopulations of tetramer-binding cells that had little to no surface CD8 were detected in situ both early and late post-infection, and in both vaginally and rectally inoculated macaques. These tetramer(+)CD8(low/-) cells were more often localized in apparent B cell follicles relative to T cell zones and more often found near or within the genital epithelium than the submucosa. Cells analyzed by flow cytometry showed similar populations of cells. Further immunohistological characterization revealed small populations of tetramer(+)CD20(-) cells inside B cell follicles and that tetramer(+) cells did not stain with gammadelta-TCR nor CD4 antibodies. Negative control tetramer staining indicated that tetramer(+)CD8(low/-) cells were not likely NK cells non-specifically binding to MHC tetramers. These findings have important implications for SIV-specific and other antigen-specific T cell function in these specific tissue locations, and suggest a model in which antigen-specific CD8+ T cells down modulate CD8 upon entering B cell follicles or the epithelial layer of tissues, or alternatively a model in which only antigen-specific CD8 T cells that down-modulate CD8 can enter B cell follicles or the epithelium.